2023
DOI: 10.1007/s13318-023-00815-x
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic, Safety, and Tolerability Trial of Palovarotene in Healthy Japanese and Non-Japanese Participants

Abstract: Background and ObjectivePalovarotene is an oral, selective retinoic acid receptor gamma agonist under investigation for fibrodysplasia ossificans progressiva (FOP). Palovarotene is primarily metabolized by cytochrome P450 (CYP) 3A4. Differences in CYP-mediated metabolism of CYP substrates have been observed between Japanese and non-Japanese individuals. This phase I trial (NCT04829786) compared the pharmacokinetic profile of palovarotene in healthy Japanese and non-Japanese participants and evaluated the safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Generalizability may also be limited since this trial was conducted at a single center in the US. However, pharmacokinetic phase I trials are typically conducted at a single site, and an ethnic sensitivity trial found no differences in the pharmacokinetics and safety of palovarotene between healthy Japanese and non-Japanese participants [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generalizability may also be limited since this trial was conducted at a single center in the US. However, pharmacokinetic phase I trials are typically conducted at a single site, and an ethnic sensitivity trial found no differences in the pharmacokinetics and safety of palovarotene between healthy Japanese and non-Japanese participants [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of palovarotene was assessed in a double-blind, randomized, crossover, single-dose phase I trial in Japan with both local and international healthy participants. The results showed that palovarotene was well tolerated and metabolized identically in both Japanese and non-Japanese individuals, indicating its potential for global effectiveness and applicability [9]. Two trials studied the efficacy of palovarotene in patients with FOP.…”
Section: Palovarotene Approved As First Treatment For Fibrodysplasia ...mentioning
confidence: 99%